The telework performance dilemma: exploring the role of trust, social isolation and fatigue - Ficapal-Cusi, Pilar; Torrent-Sellens, Joan; Palos-Sánchez, Pedro R; González-González, Ines (International Journal of Manpower, 2023)
Purpose: Due to the crisis originated by the COVID-19 pandemic, an important number of workers have been incorporating the telework modality. In this context, the distance from the workplace generates new dilemmas for work performance. In the paper the authors study the role of some individual and social antecedents on telework outcomes. In particular, they empirically investigate the direct relationship between trust (TR) and telework performance (PER) and explore mediators of that relationship such as social isolation (SI) and fatigue (FA). Design/methodology/approach: A theoretical model with three main hypotheses is proposed and tested using partial least square structural equation modeling (PLS-SEM). The study sample, of an exploratory nature, consists of a dataset of 201 teleworkers working in Spanish companies. Findings: The relevance of the proposed model is demonstrated and FA is found to be the factor that most affects (negatively) PER, followed by TR (positively) and SI (negatively). Beyond the direct effects, the results provide support for the role of SI and FA in mediating the relationship between TR and PER. Originality/value: This paper discusses the PER dilemma and proposes and tests a background model that may be useful for future research. The results are of interest to human resource managers, consultants, academics and telework tool developers and managers. Practices are proposed to improve TR or to reduce feelings of SI or FA. The research provides a practical evaluation tool for telework implementation.
Keywords: fatigue; PLS-SEM; social isolation; telework dilemma; telework performance; trust; work overload; Scopus; JCR